A novel strategy for analyzing aptamer dominated sites and detecting AFB1 based on CRISPR–Cas12a. Issue 1 (21st November 2022) - Niu, Chenqi; Xing, Xinhui; Zhang, Chong
Abstract : We proposed a novel strategy for analyzing aptamer dominated sites and a AFB1 biosensor was developed based on the results. Abstract : Profiling of aptamer dominated sites which have a huge impact on aptamer affinity is essential to characterize the relationship between an aptamer and target molecule and show the potential for boosting the sensitivity of aptamer-based biosensors. Here, we report a novel strategy to analyze aptamer dominated sites and detect aflatoxin B1 (AFB1) based on CRISPR–Cas12a. 28 different crRNAs were designed to hybridize with every region of the AFB1 47-nt aptamer, and sites 24–26 from the 5′ to 3′ end in the aptamer ("TGT") were speculated to be the dominated sites according to the different responses based on the fluorescence intensity inhibition rate. Then, this was verified by replacing the three bases through the BLI assay. Three-dimensional (3D) modeling and molecular docking were also used to laterally validate the results. Moreover, the effects of special structures of DNA on the activated Cas12a trans -cleavage activity were evaluated to enrich our understanding of Cas12a. In addition, a strategy for the detection of AFB1 based on Cas12a was developed. The workflow is convenient, simple, and rapid (37 °C in 20 min) with a detection limit of 0.8 ng mL −1 . The strategy presented good specificity over other mycotoxins and aflatoxin analogues and showed potential in complex sample analysis.